When the Known Well May Sell: The Interaction of Familiarity and Choice Numeracy on Satisfaction with a Streaming Video on Demand Recommendation Interface - Fisher, Nathan; Lee, Hyelim; Flansburg, Glenn (Journal of Telecommunications and the Digital Economy, 2025)
While Streaming Video on Demand (SVOD) consumers may express a desire for unlimited new and novel choices, excess choice can cause anxiety and choice overload. Further, familiarity can also influence perceptions of available choices. Addressing a gap in the literature on familiarity’s interaction with choice numeracy in an SVOD recommendation environment, this 2x2 experiment examines effects of choice-set size of TV sitcoms on potential use/perceptions of SVOD platforms and to what extent familiarity with the choices interacts with those perceptions through examining differences and interactions between small vs large choice sets, and familiar vs non-familiar shows. Familiarity tends to override potential choice overload effects and non-familiarity tends to exacerbate negative effects associated with too much choice, which has implications for purveyors of not only SVOD systems but other digital applications with similar recommendation systems, such as music streaming and podcasts, to emphasise choices that are likely to have familiarity to consumers, especially when interfaces themselves may be unfamiliar.